1987
DOI: 10.1002/path.1711520209
|View full text |Cite
|
Sign up to set email alerts
|

Morphological observations on the gallbladder of ground squirrels fed a lithogenic diet

Abstract: Richardson's ground squirrels (Spermophilus richardsonii) of both sexes were fed a 2 per cent cholesterol-enriched rat chow diet for intervals of 1, 2, 10 and 20 weeks. Light microscopy and 3H-thymidine autoradiography revealed an increase in cell proliferation prior to the occurrence of macroscopically visible stones, but in the presence of crystals and microliths. Transmission electron microscopy studies showed that columnar epithelial cells undergo mitosis rather than basal cells and that oedematous cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…MacPherson et al (1987) documented the chronology of experimental cholelithiasis in the Richardson's ground squirrel (Spermophilus richardsonii) with scanning electron microscopy. Further investigation into the ultrastructural events exhibited during the chronological development of gallstones using this model revealed mucus hypersecretion (Pemsingh et al, 1987a), lipid accumulation in the mucosa (Pemsingh et al, 1988) as well as increases in cell proliferation, and occurrence of hyperplasia and Rokitansky-Aschoff sinuses during the 20 week experimental period (Pemsingh et al, 1987b). Smith et al (1987) reviewed the model as reported by MacPherson et al (1987) and indicated its great potential based on the very early occurrence of mucus hypersecretion and the ability to modify this response by varying the cholesterol content of the diet.…”
Section: Introductionmentioning
confidence: 93%
“…MacPherson et al (1987) documented the chronology of experimental cholelithiasis in the Richardson's ground squirrel (Spermophilus richardsonii) with scanning electron microscopy. Further investigation into the ultrastructural events exhibited during the chronological development of gallstones using this model revealed mucus hypersecretion (Pemsingh et al, 1987a), lipid accumulation in the mucosa (Pemsingh et al, 1988) as well as increases in cell proliferation, and occurrence of hyperplasia and Rokitansky-Aschoff sinuses during the 20 week experimental period (Pemsingh et al, 1987b). Smith et al (1987) reviewed the model as reported by MacPherson et al (1987) and indicated its great potential based on the very early occurrence of mucus hypersecretion and the ability to modify this response by varying the cholesterol content of the diet.…”
Section: Introductionmentioning
confidence: 93%
“…Increased cellular proliferation was another feature observed in the response of ground squirrel gallbladder epithelium to a cholesterol-enriched diet. Mitotic and labeling indices of gallbladder epithelium increased during the early phases, independent of and preceding stone formation, distention and inflammatory changes (34).…”
Section: Fig 2 Labeled Mucus Granules (Arrow) and Endoplasmic Reticmentioning
confidence: 94%
“…Hypersecretion of epithelial mucins prior to cholesterol monohydrate crystal precipitation, a pattern of stone formation similar to man (22), and a concomitant increase in cellular proliferation and eventual mucosal damage as the experimental period progresses (34), have all been shown to be features of the Richardson's ground squirrel-cholesterol model. These similarities indicate the model has great potential in the evaluation of factors which promote or inhibit gallbladder disease and its treatment.…”
Section: Fig 2 Labeled Mucus Granules (Arrow) and Endoplasmic Reticmentioning
confidence: 99%
“…Hypercholesterolemia was induced in the animals by giving cholesterol (Sigma Chemical Co., St. Louis, USA) mixed with the rabbit chow pellet (2% cholesterol, w/w, in food pellet) [5]. For each 100 g of ground rabbit chow pellet, 2 g of cholesterol were added and mixed with a little sterile distilled water.…”
Section: Methodsmentioning
confidence: 99%